Functional Decline and Resilience in Older Women Receiving Adjuvant Chemotherapy for Breast Cancer. Issue 5 (26th August 2018) - Hurria, Arti; Soto‐Perez‐de‐Celis, Enrique; Allred, Jacob B.; Cohen, Harvey Jay; Arsenyan, Anait; Ballman, Karla; Le‐Rademacher, Jennifer; Jatoi, Aminah; Filo, Julie; Mandelblatt, Jeanne; Lafky, Jacqueline M.; Kimmick, Gretchen; et al.
Abstract : Objectives: To analyze self‐reported changes in physical function in older women with breast cancer receiving adjuvant chemotherapy. Design: Secondary analysis of the Cancer and Leukemia Group B (CALGB) 49907 prospective randomized clinical trial. Setting: CALGB institutions in the United States. Participants: Women aged 65 and older with Stage I to III breast cancer enrolled in CALGB 49907 who had physical function data from before and after receipt of adjuvant chemotherapy (N=256; mean age 71.5, range 65–85). Measurements: Participants were administered the physical function subscale of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire before chemotherapy, at the end of chemotherapy, and 12 months after chemotherapy initiation. Functional decline was defined as a more than 10‐point decrease from baseline at each time point. Resilience was defined as return to within 10 points of baseline. Multivariable regression was used to examine pretreatment characteristics associated with physical function changes. Results: Of 42% of participants who had physical function decline from before to the end of chemotherapy, 47% recovered by 12 months (were resilient). Almost one‐third experienced functional decline from before chemotherapy to 12 months later. Pretreatment fatigue was a risk factor for functional decline from before to the end of chemotherapy ( P =.02). Risk factors for functional decline at 12 months included pretreatment dyspnea ( P =.007) and being unmarried ( P= .01). Conclusion: Functional decline was common in older women receiving adjuvant chemotherapy for breast cancer in a clinical trial. Although half recovered their physical function, one‐third had a clinically meaningful decline at 12 months. Strategies are needed to prevent functional decline in older adults receiving chemotherapy. J Am Geriatr Soc 67:920–927, 2019.